Треворова адаптація Джойсового імпульсу - Кабкова, О. (Слово і Час, 2021)
Вільям Тревор не уник впливу доробку Дж. Джойса на власну творчість.
Можна окреслити кілька рівнів присутності ірландського класика в його
текстах: Джойс як персонаж, як зразок для творчої діяльності, як версія для стилізації та навіть розігрування. Новели «Музика», «Третій
зайвий», «Ще два кавалери» В. Тревора травестійно пов’язані з оповіданнями зі збірки «Дублінці» Дж. Джойса (на рівнях фабули, образів
персонажів, художнього простору, особливостей нарації, концентрованої
поетичної образності). While finding out the relation of W. Trevor’s writing to Joyce, we are to take into account
the fact, fixed by the German writer H. Bell in his “Irish diary”: Joyce is one of the ordinary
surnames in Ireland.
Yet the aim of the article was to search for the influence of the literary technique of
J. Joyce — one of the well-known modernists — on W. Trevor’s creative works. On the one
hand, W. Trevor himself in the interviews insisted that “Dubliners” and “A Portrait of the
Artist as a Young Man” were valuable for him within the whole life; on the other hand, the
known and famous writers and critics aimed at finding those links. A number of researchers
took into account that Joyce’s later texts were not so valuable for Trevor’s creative works. His
influence was not the linguistic pyrotechnics of the “Ulysses” but the modest and punctilious
voice of “Dubliners”.
It is possible to determine some levels of Joyce’s presence in W. Trevor’s texts: Joyce as a
character, as a model of creative activity, as a pattern for stylization and even comic imitation.
One of the characters of Trevor’s “Music” was fascinated with Joyce’s appearance, his
photograph. Sometimes, while hearing music, he was imagining himself a human being
similar to Joyce. “The Th ird Party” began with a meeting of two men, one the husband,
one the lover in a Dublin hotel bar. They have to come to an agreement on the end of the
marriage, which was not achieved. The plot of this story is somewhat a travesty of “A Little
Cloud” (from “Dubliners”). Moreover, the main characters are W. Trevor’s version of two
different types of mental constitution vivid in “A Little Cloud” as well as in “Ulysses”. The
interview of two characters in Trevor’s text allowed using Joyce’s telling strategy: an application
of subjective third-person narration. An aspect of location in Trevor’s story is similar
to that of Joyce, it is Dublin. Nevertheless for Trevor Dublin was a city, where events took
place, not a version of the important original location, as it was with Joyce. The same may
be said about “Two More Gallants”. Th is story of the modern and equally traditional Irish
writer is the most vivid example of the author’s dialogue with the original text of Joyce. The
writer simultaneously reflected and parodied “Two Gallants” (from “Dubliners”). There is a
certain similarity between the viewpoints of both authors on Dublin and Ireland in general.
The creative activity of Joyce was governed by Ireland. W. Trevor’s links with Ireland were
restored only when he became something of a stranger to this country. Moreover, Trevor’s
conception of Ireland remained constant as if nothing had happened in this country during
the second half of the XX century. So the reality of “Two Gallants” and “Two More Gallants”
remained alike, as well as irresponsibility of the main characters.
The narrative nerve in Joyce’s text may be defined as no-event, while Trevor’s text is
arranged according to tale tradition. “Two Gallants” is associated with the concentrated poetic
image of paralysis. A similar representation is evident in “Two More Gallants”: puppets
dance to the music of original sins. Th at shows Trevor’s play with the original text.